Eco-Transcendence: Reconfiguring MetaReality to Rethink the Climate Crisis - Fidelis Oktovianus Sanbein; Siti Murtiningsih; Lailiy Muthmainnah (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Mainstream readings of the climate crisis remain anthropocentric and rarely address the ecological relationality that constitutes oikos, the shared home of human and more-than-human life. Environmental science, policy, and ethics tend to reduce the crisis to technical and governance problems, leaving its causal-transcendental structures, the deep conditions that enable the crisis, unexamined.Objective: This study aimed to reconfigure the causal ontology of Roy Bhaskar’s MetaReality in an ecological direction and to formulate eco-transcendence as a new ontological framework for understanding the climate crisis.Methods: Using library research on Bhaskar’s MetaReality-phase writings and recent climate literature, this qualitative philosophical study applied hermeneutic reading, immanent critique, ontological retroduction, and conceptual reconstruction. Ontological retroduction was used to infer the conditions that reality must satisfy for the climate crisis to occur.Results: The climate crisis appeared not merely as an emissions or policy problem, but as an ontological disjuncture between stratified reality and the unified ground of MetaReality, marked by ontological alienation, the severing of human practice from this ground, and the erosion of oikos habitability. The novelty of eco-transcendence lay in its integration of causality, ecological existence, and ethical responsibility within a single horizon, thereby grounding transformative praxis beyond technocracy and abstract moralism.Conclusion: A metarealistic ecological ontology was therefore not merely desirable but a transcendental prerequisite for adequately addressing the climate crisis.